Living by the land, gazing at the sea: Hominin occupation of near-coastal landscapes on the western periphery of the Red Sea - Amanuel Beyin (Quaternary Science Advances)
The paper examines recently reported Acheulean and Middle Stone Age archaeological occurrences in near-coastal plains on the western periphery of the Red Sea (Sudanese coast) with the aim of illuminating the role of the region in hominin survival, and possibly as an out-of-Africa dispersal conduit. Using a Viewshed analysis in ArcGIS, the study sought to assess the extent to which the seashore may have been visible from the archaeology-bearing localities during conditions similar to the present or those more humid interglacial phases than today. The purpose of the Viewshed analysis is to gauge the range of habitat-options hominins had on the western periphery of the Red Sea. The result demonstrates that the seashore would have been visible from most of the archaeological sites. Thus, it is reasonable to surmise that the coastal margin may have remained an integral part of the space exploited by the hominins that inhabited the nearby inland plains. However, the observation cannot be regarded as attesting all the areas deemed visible were necessarily exploited by hominins. Overall, the archaeological evidence from the study area broadens our understanding of the range of environments hominins occupied in Africa prior to and during their expansion to Eurasia. A proximate goal of the paper is to drive archaeological research attention to near-coastal landscapes, as such places may provide a potent vantage point to assess hominin engagement with the seashore. I conclude with an appeal to the paleoanthropological community to expand field-centered research to the vast understudied regions of Africa so as to capture hominin experiences across diverse ecosystems of the continent. Only then will we be able to discern hominin biogeographic range at different periods and theorize about the ecological drivers of our species' success.